2019
DOI: 10.3389/fpsyg.2018.02708
|View full text |Cite
|
Sign up to set email alerts
|

Deconstructing Procedural Memory: Different Learning Trajectories and Consolidation of Sequence and Statistical Learning

Abstract: Procedural learning is a fundamental cognitive function that facilitates efficient processing of and automatic responses to complex environmental stimuli. Here, we examined training-dependent and off-line changes of two sub-processes of procedural learning: namely, sequence learning and statistical learning. Whereas sequence learning requires the acquisition of order-based relationships between the elements of a sequence, statistical learning is based on the acquisition of probabilistic associations between el… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
135
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(140 citation statements)
references
References 61 publications
(112 reference statements)
4
135
0
1
Order By: Relevance
“…Statistical learning is the ability to extract regularities, or frequencies, from environmental input and may play an important role in language learning (Orbán et al 2008;Turk-Browne et al 2010), whereas sequence learning is defined as the acquisition of temporal order information in a series of stimuli (Nemeth et al 2011). These may rely on different brain substrates (Rose et al 2011;Kóbor et al 2018;Simor et al 2019), follow different learning curves (Simor et al 2019), and are differentially affected by sleep (Doyon et al 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…Statistical learning is the ability to extract regularities, or frequencies, from environmental input and may play an important role in language learning (Orbán et al 2008;Turk-Browne et al 2010), whereas sequence learning is defined as the acquisition of temporal order information in a series of stimuli (Nemeth et al 2011). These may rely on different brain substrates (Rose et al 2011;Kóbor et al 2018;Simor et al 2019), follow different learning curves (Simor et al 2019), and are differentially affected by sleep (Doyon et al 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…34 Another study reported that both sleep and resting wakefulness (with alerting tones administered to maintain wakefulness) similarly benefitted performance on an auditory sequencelearning task, in comparison to active wake. 33 Yet other recent studies have compared sleep, active wake, and quiet wake and found no difference between conditions (including, perhaps surprisingly, no difference between sleep and active wakefulness) for an alternating serial reaction time task 35 and a paired associates task. 36 While the above findings suggest that wakefulness and sleep might show equivalent memory benefits under some conditions, a direct comparison of the memory effects of sleep to those of completely task-and stimulus-free eyes closed rest has not yet been conducted.…”
Section: Introductionmentioning
confidence: 93%
“…Thus, greater serial-order learning was determined as faster responses to pattern vs. random high trials. Note that in previous ASRT studies, serial-order learning was often referred to as sequence learning (Nemeth et al, 2013;Simor et al, 2019). Statistical learning was measured by the difference in RTs between random low and random high trials (that is, the average RTs for random low trials minus the average RTs for random high trials).…”
Section: Taskmentioning
confidence: 99%
“…For the analysis of the cued ASRT, we followed procedures outlined in previous studies (Howard and Howard, 1997;Song et al, 2007;Nemeth et al, 2013;Simor et al, 2019). First, the blocks of the task were collapsed into epochs of five blocks to facilitate data processing and to increase statistical power.…”
Section: Behavioral Datamentioning
confidence: 99%